2020
DOI: 10.9770/jesi.2020.7.3(42)
|View full text |Cite
|
Sign up to set email alerts
|

How the nexus among the free trade, institutional quality and economic growth ffect the trade from ASEAN countries

Abstract: The main purpose of the study is to answer the research question that How the nexus among the free trade, institutional quality and economic growth effect the trade from ASEAN countries. The exports become uncompetitive because of such hidden tax and high production costs in ASEAN. It can be said that importer/importers can achieve competitive advantage by being involve in corrupt activities as compared to others who are not willing to give bribes. The trade can be enhanced or hindered through corruption based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Asian countries, on one hand, are progressive and fast growing regions in terms of industrialization, urbanization, globalization, and population. On the other hand, they significantly contribute adversely to global pollution, climate change, and environment degradation [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Asian countries, on one hand, are progressive and fast growing regions in terms of industrialization, urbanization, globalization, and population. On the other hand, they significantly contribute adversely to global pollution, climate change, and environment degradation [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…This eliminates uncertainty and the costs associated with transactions, which encourages investment on both the domestic and international levels. A climate that is friendly to business helps foster innovation and entrepreneurship, which in turn leads to the expansion of the economy and the creation of new jobs (Chen et al, 2021). The trust of investor is boosted by high standards of regulatory quality (Yeboua, 2021).…”
Section: Panel Ardl Resultsmentioning
confidence: 99%
“…However, recently over the past few decades, both SAFTA and ASEAN are taking measures to promote foreign investments to improve economic stability, technology transfer, and resource flow in the region. For providing a favorable environment to foreign investors, the SAFTA and ASEAN regions have relaxed the export-import rules by making necessary policy amendments (Regmi et al, 2017;Chetthamrongchai et al, 2020). In addition, these countries have steered trade sanction laws and provided attractive financial Besides welcoming unilateral FDI, Thailand, Vietnam, and Cambodia have become signatories to different bilateral trade agreements as well (Ratna et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bayar et al (2020) showed that competition has intensified financial direct investment flows in recent decades, which are an important source to increase economic competitiveness. Chetthamrongchai et al (2020) focused on the factors influencing the non-competitiveness of foreign trade and economic growth. Their results reported that the negative factors influencing the variables of interest were corruption, political instability and the limited quality of state institutions.…”
Section: Brief Taxonomy Regarding the Impact Of Financial Direct Inve...mentioning
confidence: 99%